2019
DOI: 10.1177/1553350618822077
|View full text |Cite
|
Sign up to set email alerts
|

Articulated Instruments and 3D Visualization: A Synergy? Evaluation of Execution Time, Errors, and Visual Fatigue

Abstract: Objective. The introduction of advanced endoscopic systems, such as the Storz Image1S and the Olympus Endoeye, heralds a new era of 3-dimensional (3D) visualization. The aim of this report is to provide a comprehensive overview of the neurophysiology of 3D view, its relevance in videoscopy, and to quantify the benefit of the new 3D technologies for both rigid and articulated instruments. Method. Sixteen medical students without any laparoscopic experience were trained each for a total of 27 hours. Proficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, for both operator groups enrolled in this study, accurate suture placement on the target was difficult, because the instrument bent at the shaft during the maneuvers and the force applied was not efficient in terms of completing bites or passing the needle through the tissue. It is likely that the stiffness of the distal bending section should be improved to avoid loss of energy through the shaft; in fact, when using rigid instruments, the distance from the handle to the tip is constant, improving the transmission of the force needed to place the needle [18]. Moreover, a rigid shaft follows the wrist supination, improving the efficacy of forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for both operator groups enrolled in this study, accurate suture placement on the target was difficult, because the instrument bent at the shaft during the maneuvers and the force applied was not efficient in terms of completing bites or passing the needle through the tissue. It is likely that the stiffness of the distal bending section should be improved to avoid loss of energy through the shaft; in fact, when using rigid instruments, the distance from the handle to the tip is constant, improving the transmission of the force needed to place the needle [18]. Moreover, a rigid shaft follows the wrist supination, improving the efficacy of forces.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because they allow for more degrees of freedom, steerable instruments provided help in needle positioning on the straight needle holder jaws and also in grasping the edge of the tissue for a proper and precise bite. With steerable instruments, the distal part is mostly positioned perpendicular to the viewing direction [18]. The two additional degrees of freedom of tip deflection and rotation were useful for difficult access angles to the operative field [13].…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques reported in the literature for decreasing eyestrain include reducing rapid zoom movements and using newer endoscopes with articulations for improved stability, closing one eye temporarily when advancing through narrow corridors, and having adequate smoke evacuation to prevent visual conflicts created by smoke particles close to the lens. 31,32 We conclude that 3D endoscopy has comparable safety to 2D endoscopy based on performance time and complications rates. In addition, 3D endoscopy may also have the potential for superior efficiency to 2D endoscopy as demonstrated by a reduction in performance time and error rate in simulation-based studies.…”
Section: Clinical Safety and Efficacy Of 3d Endoscopymentioning
confidence: 74%
“…Artificially induced binocular parallax from stereoscopic images can have accommodation-vergence conflicts that leads to visual symptoms. 31 While three studies reported visual fatigue, blurring and headache, performance or operative time were not impacted. 2,17,20 There is likely a dedicated learning curve, even for well-trained surgeons, to develop a different gaze strategy to process 3D images.…”
Section: Clinical Safety and Efficacy Of 3d Endoscopymentioning
confidence: 94%